Can Traditional Authority Improve the Governance of Forestland and Sustainability? Case Study from the Congo (DRC) - Majambu, E.; Mampeta Wabasa, S.; Welepele Elatre, C.; Boutinot, L.; Ongolo, S. (MDPI, 2019)
With about 107 million hectares of moist forest, the Democratic Republic of Congo (DRC) is a perfect paradox of a natural resources endowed country caught in repeated economic and socio-political crises. Democratic Republic of Congo possesses about 60% of the Congo basin’s forest on which the majority of its people rely for their survival. Even if the national forest land in the countryside is mainly exploited by local populations based on customary rights, they usually do not have land titles due to the fact that the state claims an exclusive ownership of all forest lands in the Congo basin including in DRC. The tragedy of “bad governance” of natural resources is often highlighted in the literature as one of the major drivers of poverty and conflicts in DRC. In the forest domain, several studies have demonstrated that state bureaucracies cannot convincingly improve the governance of forestland because of cronyism, institutional weaknesses, corruption and other vested interests that govern forest and land tenure systems in the country. There are however very few rigorous studies on the role of traditional leaders or chiefdoms in the governance of forests and land issues in the Congo basin. This research aimed at addressing this lack of knowledge by providing empirical evidence through the case study of Yawalo village, located around the Yangambi Biosphere Reserve in the Democratic Republic of Congo. From a methodological perspective, it used a mixed approach combining both qualitative (field observations, participatory mapping, interviews, focal group discussions, and desk research,) and quantitative (remote sensing and statistics) methods. The main findings of our research reveal that: (i) vested interests of traditional rulers in the DRC countryside are not always compatible with a sustainable management of forestland; and (ii) influential users of forestland resources at the local level take advantage of traditional leaders’ weaknesses—lack of autonomy and coercive means, erratic recognition of customary rights, and poor legitimacy—to impose illegal hunting and uncontrolled forest exploitation.